Evaluating the effectiveness of labor market interventions on reducing the impacts of the COVID‐19 pandemic. Issue 1 (28th September 2022) - Elgin, Ceyhun; Williams, Colin; Öz Yalaman, Gamze
Abstract: This paper evaluates whether different labor market policy interventions taken in response to the COVID‐19 pandemic have been effective in reducing its adverse impacts. We construct a database covering 165 countries and 39 labor market interventions grouped into four pillars: stimulating the economy and jobs (pillar 1); supporting enterprises, employment, and incomes (pillar 2); protecting workers (pillar 3); and social dialogue (pillar 4). The results revealed that measures taken under pillars 1, 2, and 3 have reduced the impacts of the pandemic on economic growth; measures under pillar 4 were significantly associated with reducing its impacts on employment and those under pillar 2 with reducing its impacts on working hours.